Aspect Ratio Effect on Convective Heat Transfer of Radially Outward Flow in Rotating Rectangular Ducts - C. R. Kuo; G. J. Hwang (International Journal of Rotating Machinery)
Experiments were conducted to investigate the effects of rotation and aspect ratio on the convective heat transfer of radially outward air flows in rotating rectangular ducts with a uniform wall heat flux by using fiberglass duct walls lined with separated film heaters. The duct hydraulic diameter, heater active length, and mean rotation radius were 4, 120, and 180 mm, respectively. Ranges of parameters were through-flow Reynolds number, 1,000–15,000; rotation number, 0–0.32; rotational buoyancy parameter, 0–1.2; and cross-sectional aspect ratio, 0.5, 1.0, and 2.0. The results showed that the higher the rotation number, the greater the enhancement ofthe heat transfer rate especially at the pressure side. The rotational buoyancy parameter decreases the heat transfer for low Re but enhances the heat transfer for high Re. The largest heat transfer enhancement is seen for AR = 1.0, and the enhancement for AR = 0.5 is greater than that for AR = 2.0.